Stilistika Pantun Dalam Pertunjukan Dambus - Septiani, Yeni; Armariena, Dian Nuzulia; Masnunah, Masnunah (UPI, 2020)
The research aims to determine and describe the stylistics that focus on language style and imaging in the pantun of Dambus. This research uses descriptive qualitative method. Data sources from this study consisted of 4 informants. The techniques used in collecting data are observation, record, interview, and note-taking techniques. The results of the analysis obtained by researchers in the form of language styles amounted to 10 language styles according to their understanding and usefulness, namely, the style of parables, personification, antithesis, hyperbole, paronomasia, euphemism, alliteration, anaphora, anadiplosis, and asonation. While the images in the dambus performance rhymes are 4 images, they are vision, hearing, smell and taste. The use of this pantun will function as it should if someone wants to use it during a dambus performance in circumcision or marriage events. If there are words that make the listener offended in pantun, it is no more than just entertainment, and if there are positive words that can be taken for introspection as well as learning in the field of literature.AbstrakPenelitian ini bertujuan untuk mengetahui dan mendeskripsikan stilistika yang memusatkan pada gaya bahasa dan pencitraan pada pantun petunjukan Dambus. Penelitian ini menggunakan metode kualitatif deskriptif. Sumber data dari penelitian ini terdiri dari 4 orang informan. Teknik yang digunakan dalam mengumpulkan data adalah teknik observasi, rekam, wawancara, dan catat. Hasil analisis yang didapatkan oleh peneliti adalah berupa gaya bahasa berjumlah 10 gaya bahasa sesuai dengan pengertian dan kegunaannya yaitu, gaya bahasa perumpamaan, personifikasi, antitesis, hiperbola, paronomasia, eufemisme, aliterasi, anafora, anadiplosis, dan asonasi. Sedangkan citraan pada pantun pertunjukan dambus berjumlah 4 citraan, yaitu citraan penglihatan, pendengaran, penciuman, dan pencecapan. Penggunaan pantun ini akan berfungsi sebagai mana mestinya apabila seseorang ingin menggunakannya pada saat pertunjukan dambus dalam acara khitanan maupun perkawinan. Jika dalam pantun pertunjukan dambus terdapat kata-kata yang membuat pendengar tersinggung itu tidak lebih hanya sekedar hiburan, dan jika ada kata-kata yang positif dapat diambil untuk mengintrospeksi diri maupun sebagai pembelajaran dalam bidang sastra.